1986
DOI: 10.1002/pen.760261205
|View full text |Cite
|
Sign up to set email alerts
|

An injection molding study. Part I: Melt and barrel temperature dynamics

Abstract: The dynamics of the key variables in the plastication phase of injection molding were studied using a microcomputer controlled laboratory scale injection molding machine. Interfaces for the measurement and manipulation of suitable variables were developed. An approximate theoretical analysis provided a preliminary understanding of the effect of a step input in heating power on melt and barrel temperatures. Deterministic and stochastic models were derived from experimental data for the melt and the front and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Kamel et al [2] demonstrated interaction between zone melt temperatures. This indicated conductive heat flow between the barrel and nozzle heating zones as well as heat transfer through the barrel casing.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Kamel et al [2] demonstrated interaction between zone melt temperatures. This indicated conductive heat flow between the barrel and nozzle heating zones as well as heat transfer through the barrel casing.…”
Section: Introductionmentioning
confidence: 98%
“…The models derived for melt temperature control simulations neglected these interactions and were therefore single input single output (SISO). The resulting temperature oscillations during closed loop control with SISO [2][3][4][5] can result in thermal deterioration in the polymer and longer operator setup times on the IMM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3−6 Control techniques commonly used for melt temperature control are either basic on-off control or proportional, integral and derivative (PID) based methods. 3 However, these control strategies can be unsuitable due to a lack of robustness and adaptability, which are necessary for controlling nonlinear and coupled processes. 7 Dubay 6 implemented a predictive method for controlling melt temperature, resulting in good control performance having zero overshoot.…”
mentioning
confidence: 99%